Copper(I) Iodide Promoted [3+2]-Cycloaddition/Oxidation to Construct Pyrrolo[2,1-a]isoquinolinoquinones from Naphthoquinones and Tetrahydroisoquinolines - Yu, Zihua; Tang, Xue; Huang, Chenxi; Shang, Yehan; Ye, Qing; Han, Liang; Li, Yujin (Synlett, 2022)
A copper-catalyzed, three-component, one-pot, 1,3-dipole cycloaddition/oxidation has been developed to construct pyrrolo[2,1-a]isoquinolinoquinone derivatives, with environmentally friendly oxygen as the oxidant. The pyrrolo[2,1-a]isoquinolinoquinone products were obtained from naturally available tetrahydroisoquinolines, 1,4-naphthoquinones, and benzaldehydes in medium yields.
Keywords: pyrroloisoquinolinoquinones; copper catalysis; tetrahydroisoquinolines; [3+2]-cycloaddition; oxidation; multicomponent reaction